Luxembourg : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper provides a quantitative assessment of the long-term prospects of the Luxembourg pension system and analyzes possible reform options. The results indicate a need to adopt-at an early stage and while the problems are still relatively tractable-measures to dampen the growth of pension expenditure. Otherwise, there is a risk that rising taxes or deficits could have detrimental effects on incentives for work, investment, and innovation, and result in an unsustainable slowdown of economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet